Endoscopic valve removal >180 days since implantation in patients with severe emphysema - Gompelmann, Daniela; Kontogianni, Konstantina; Schuhmann, Maren; Eberhardt, Ralf; Herth, Felix; Polke, Markus (Respiration, 2018)
Background: Valve implantation provides a reversible effective therapy in a selected group of emphysema patients. Knowing predictors for successful therapy, the rate of treatment failure has decreased. Some patients, however, do not benefit, so that the valves may have to be removed. Objectives: To assess implant-related events, complications during valve removal, and clinical outcome after endoscopic procedure. Methods: The data of 76 consecutive emphysema patients who underwent valve removal > 6 months since implantation were collected. Results: Seventy-six patients (mean age 62 years, 54% male) underwent removal of all valves after a mean time of 624 days (193-3,043 days) since implantation. Granulation tissue was observed in 39.5% (30/76) and significant secretion in 34.2% (26/76). In 5.3% (4/76), valve removal was complicated requiring another bronchoscopy in 2 of them. In 5.3% (4/76) of the patients, one valve could not be removed and remained in situ. Bleeding requiring intervention occurred in 3.9% (3/76) during valve removal. Following bronchoscopy, there was a need for antibiotics in 34.2% (26/76), glucocorticosteroids in 1.3% (1/76), and both in 6.6% (5/76) due to productive cough or chronic obstructive pulmonary disease (COPD) exacerbation. Due to respiratory failure, invasive ventilation or noninvasive ventilation was necessary in 2.6% (2/76) and 6.6% (5/76), respectively, following procedure. No statistical significant change in lung function was observed following valve removal. Conclusions: Valve removal after > 6 months since implantation is feasible and associated with an acceptable safety profile. However, close monitoring of these patients with limited pulmonary reserve is recommended with particular attention to COPD exacerbations and respiratory failure.
Gesehen am 13.05.2019